Horay Course Review Learning Model to Improve Learning Outcomes - Mei Laili Dwi Kartika Sari; Dholina Inang Pambudi (International Journal of Learning Reformation in Elementary Education, 2022)
This study aims to use Horay's Course Review learning model in 5th-grade students on natural resource learning materials to improve student learning outcomes. The type of research used is classroom action research. The design of this study is based on the Kemmis & Taggart model with four stages: planning, implementation, observation, and reflection. The variable measured is learning outcomes. The data collection techniques used are observation, tests, and documentation. The success criteria were seen from the increase in student learning outcomes which reached 88.46% of completed students. The completion value is at least 70%. In the procyclical activities before using the Horay Course Review learning model, the average score of student learning outcomes was 43.07. First Cycle, learning outcomes with an average score of 63.30, Second Siklus experienced an increase in learning outcomes with an average score of 66.53. It was concluded that using the Horay Course Review learning model improves student learning outcomes.